IDENTIFIKASI JENIS TUPAI (Tupaia Sp) DI KAWASAN HUTAN ADAT BUKIT SAGU DESA SUNGAI SENA KECAMATAN SILAT HILIR KABUPATEN KAPUAS HULU - Alex, .; Anwari, Sofwan; Tavita, Gusti Eva (JURNAL HUTAN LESTARI, 2017)
Bukit Sagu Community Forest, Sungai Sena Village, Silat Hilir District, Kapuas Hulu Regency is one of the forest with natural resources diversity richness. The wildlife that live and thrive in the indigenous forest is a kind of squirrel. Squirrel one of animal which important for the ecology function, so we need to do research on "Identification of the Squirrel species (Tupaia sp) In Indigenous Forest Region Bukit Sagu Sungai Sena village, Silat Hilir District of Kapuas Hulu Regency". The method used is a survey method, determining the location of the observations done purposive sampling by trapping. Identification the species of squirrel is done by means of measurement based on the Payne et. al, (1999). Method the number of squirrels have been found during the research in the area of ​​ Bukit Sagu Community Forest Sungai Sena, Village  Silat Hilir District, Kapuas Hulu Regency, namely 92 individuals, consisting of three species of squirrels, the squirrel beautiful (Tupaia splendidula) as much as 42 individual, squirrel mountain (Tupaia montana ) 11 individual, and ground squirrels (Tupaia tana) were 39 individual. Keywords:        Bukit Sagu Community Forest, Identification, Squirrel species, Sungai Sena village